2021
DOI: 10.1159/000519211
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Survival due to Chemotherapy including Paclitaxel in a Patient with Metastatic Primary Splenic Angiosarcoma

Abstract: A primary splenic angiosarcoma is a rare type of soft tissue sarcoma and is associated with an extremely poor prognosis. In this study, we describe the case of a patient who was diagnosed with metastatic primary splenic angiosarcoma and survived for about 2 years. A 62-year-old female was referred to us for the treatment of splenic angiosarcoma with disseminated intravascular coagulation (DIC) and multiple liver and bone metastases. Paclitaxel therapy resulted in recovery from DIC and enabled her to continue s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…However, the prognosis remains poor (20). Takehara M et al (21) reported that the 6-month survival rate for patients with PSA is only 20%, with rare instances of survival exceeding 2 years. Therefore, early diagnosis is crucial for the effective treatment and improved prognosis of splenic angiosarcoma.…”
Section: Discussionmentioning
confidence: 99%
“…However, the prognosis remains poor (20). Takehara M et al (21) reported that the 6-month survival rate for patients with PSA is only 20%, with rare instances of survival exceeding 2 years. Therefore, early diagnosis is crucial for the effective treatment and improved prognosis of splenic angiosarcoma.…”
Section: Discussionmentioning
confidence: 99%